ANALISIS KEBUTUHAN KENDARAAN PENGANGKUT SAMPAH BERDASARKAN RITASI DAN SKENARIO PENGANGKUTAN (STUDI KASUS : KECAMATAN BEKASI UTARA - Silvianti, Fifian
As population and its activity increase, the amount of waste generated by urban activity increases over time. Due to the large amount and volume of waste and its diverse species, if not properly managed, municipal waste will have negative impacts in the form of complex environmental problems, such as water, soil and air pollution, breeding of disease seeds, disruption of order, cleanliness and beauty of the environment. The amount of waste managed by North Bekasi District is only 12.29% of the total waste generation. This situation is caused by the inadequate availability of waste transportation vehicles resulting in waste accumulation in some areas. To overcome the high amount of waste generation it is necessary an analysis of the needs of waste transport vehicles that are effective and efficient. The purpose of this paper is to provide direction on the needs of waste transporting vehicles in the City of Bekasi, especially North Bekasi District, in order to improve the service of waste in the City of Bekasi. The method used in this research is the population projection method, the projection method of waste generation, the calculation of the needs of the waste transport vehicle, waste transport ritation optimization method and the minimizing travel distance method done for optimal route determination by using Geographic Information System (GIS) with Network Analyst (NA) feature. The result of this research is to be able to transport 70% of waste generation in North Bekasi District in 2017, the number of waste transportation units required is 14 units, in 2022 is 18 units, and in 2027 is 21 units. While to be able to transport the entire generation of waste in North Bekasi District in 2032, the number of waste transport vehicles required is 36 units, in 2037 is 42 units. In addition, with optimization of waste transport ritation and scenarios developed by, all waste generation can be transported every day so that waste services can be improved effectively and efficiently.